Handbook of Research on Contemporary Theoretical Models in Information Systems 2009
DOI: 10.4018/978-1-60566-659-4.ch025
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Historical Activity Theory

Abstract: This chapter reviews the origins, approaches and roles associated with the use of cultural historical activity theory (CHAT) in information systems (IS) research. The literature is reviewed and examples are discussed from IS and related fields of human-computer interaction (HCI), computer supported cooperative work (CSCW) and computer supported collaborative learning (CSCL), to illustrate the power of CHAT in IS research as well as its link to appropriate research methods. After explicating the value of its us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 41 publications
0
9
0
6
Order By: Relevance
“…CHAT has the potential to provide a robust meta-theoretical framework for understanding and analysing many areas of research and practice (Igira & Gregory, 2009). CHAT offers a cross-disciplinary perspective for analysing human practices as development processes in which both individual and social levels are interlinked.…”
Section: Resultsmentioning
confidence: 99%
“…CHAT has the potential to provide a robust meta-theoretical framework for understanding and analysing many areas of research and practice (Igira & Gregory, 2009). CHAT offers a cross-disciplinary perspective for analysing human practices as development processes in which both individual and social levels are interlinked.…”
Section: Resultsmentioning
confidence: 99%
“…In our research, we found that context plays an important role in choosing and playing epistemic games. In order to articulate the relevant context more fully, we sought inspiration from cultural-historical activity theory, which describes real life activities (e.g., problem solving) of individuals as they interact in a particular setting with particular goals and tools [49]. Wake [11] used culturalhistorical activity theory to identify schools and workplaces as activity systems that evolve both culturally and historically, with actions of the individual contributing to activities of community in pursuit of goals and outcomes.…”
Section: B Identification and Application Of Epistemic Gamesmentioning
confidence: 99%
“…Cultural-Historical Activity Theory (CHAT) offers a philosophical and cross-disciplinary perspective for analyzing diverse human practices as development processes in which both individual and social lev- els are interlinked [35]. With its recent emphasis on Information Systems, CHAT helps in exploring and understanding interactions in their social context, multiple contexts and cultures, and the dynamics and development of particular activities.…”
Section: Theories About Human Activity and User Scenariomentioning
confidence: 99%
“…ALI offers personalized recommendations for daily activities, based on two different sources: 1) user data: her/his context (temporal and spatial) and her/his preferences (needs, motives, activities, goals); and 2) domain expert's information. In our approach, each human activity is composed by a sequence of actions; these actions are directed by goals such as "doing physical exercise", following the hierarchical activity model of Cultural-Historical Activity Theory (CHAT) [35,44,70]. This scenario is introduced in Fig.…”
Section: Introductionmentioning
confidence: 99%